2013
DOI: 10.5603/ep.2013.0025
|View full text |Cite
|
Sign up to set email alerts
|

Reimbursement of metformin for polycystic ovary syndrome

Abstract: The latest list of reimbursed medicines includes, as a new addition, metformin for the treatment of polycystic ovary syndrome (PCOS), which is extremely important for practicing physicians. While this paper briefly summarises the current state of knowledge on PCOS, its main aim is to remind the reader about the effectiveness of metformin in women with PCOS in controlling glycaemia, increasing tissue sensitivity to insulin and affecting endothelial function, vascular inflammation, lipid profile and other risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 62 publications
0
13
0
2
Order By: Relevance
“…1). 3,11,15 Recent reports have revealed a close correlation between mental disorders and clinical PCOS symptoms such as acne, hirsutism, infertility, obesity and a poorer quality of life. A higher frequency of depression, drug-related and bipolar disorders, bulimia, anorexia or non-spe- 12 Chronic hyperandrogenemia, which leads to increased aromatization of androgens to estrogens in adipose tissue, may contribute further to the development of hormone-dependent tumors, such as endometrial, mammary or ovary neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). 3,11,15 Recent reports have revealed a close correlation between mental disorders and clinical PCOS symptoms such as acne, hirsutism, infertility, obesity and a poorer quality of life. A higher frequency of depression, drug-related and bipolar disorders, bulimia, anorexia or non-spe- 12 Chronic hyperandrogenemia, which leads to increased aromatization of androgens to estrogens in adipose tissue, may contribute further to the development of hormone-dependent tumors, such as endometrial, mammary or ovary neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the underlying causes of PCOS include increased frequency of gonadotropin-releasing hormone (GnRH) pulses that stimulate the theca cells to produce androgen; decreased levels of FSH (and thus a defect in the late luteal and early follicular phases); insulin resistance via a post-receptor defect in the fat tissue and skeletal muscles (abnormal phosphorylation of tyrosine kinase); pancreatic beta-cell dysfunction; and obesity. 1,3 It is often impossible to determine definitively what is a cause and what is an effect in the development of PCOS. In addition, it is generally recognized that obesity increases menstrual disorders and hyperandrogenism, while weight reduction reduces the clinical signs.…”
Section: Etiopathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“… 5 However, several trials have failed to observe any significant improvement in lipid profile after metformin treatment. 6 7 The use of statins has recently emerged as a novel therapeutic approach to PCOS. 8 Treatments using statins, and combined statins and metformin can effectively improve IR, fasting insulin (F-INS), insulin sensitivity index, 9 hyperandrogenemia, 10 hirsutism, acne, 11 testosterone 10 and decreasing C reactive protein (CRP).…”
Section: Introductionmentioning
confidence: 99%
“…Metformin stops proliferation of cell by by reducing the VEGF levelscontrolling neo vascularisation of tumour. At hormonal level it induces progesterone receptor thereby increasing the response to hormonal therapy [16]. glyoxalase I (GLO1), an enzyme that detoxifies methylglyoxal, is selectively overexpressed in the apoptosis-resistant cancer cells [17].…”
Section: Other Mechanism Of Anti-proliferative Activity Miscellaneousmentioning
confidence: 99%